An optimized method for synthesizing phase-pure Ti3AlC2 MAX-phase through spark plasma sintering. Issue 2 (February 2022) - Yunus, Mohammad; Kumar, Rakesh; Maji, Bikas C.; Krishnan, Madangopal
Abstract: So far many attempts have been made to synthesize phase-pure Ti3 AlC2 MAX-phase. But still the challenge posed by the presence of TiC and Ti-Al based intermetallic transient impurity phases in the final product is a persisting problem. Spark plasma sintering (SPS) technique has been the most successful method to decrease the impurity content of the final product. Even so, synthesis of phase-pure Ti3 AlC2 MAX-phase, without any TiC and Ti-Al based intermetallic impurities, has not been achieved and reported in literature with substantial evidences. Further, high purity Ti3 AlC2 MAX-phase synthesized using SPS technique has shown lack of phase and microstructural stability above 1350°C temperature. In this work, we have reported an optimized method for producing phase-pure Ti3 AlC2 MAX-phase (having more than 99 % purity) using commercial grade Ti, Al and C elemental powders through SPS technique. The final product also showed very good high temperature stability up to 1500°C under flowing Argon inert atmosphere.